Implementasi Hadis Penggunaan Sutrah (Studi Living Sunah di Lingkungan Wahdah Islamiyah): Implementation of Hadith Using Sutrah (Study of Living Sunah in the Wahdah Islamiyah Environment) - Rusdi Kasim Badang (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2026)
This research aims to examine the content, implementation and impact of the hadith of the Prophet SAW. regarding the use of the sutrah in prayer in the Wahdah Islamiyah environment. This research uses a qualitative method with a phenomenological approach and a hadith approach as a basis for text analysis and social reality. The results of the research show that the hadiths about the sutrah emphasize the strong recommendation to use the sutrah when praying, both when staying and traveling. The hadith content also displays the dimensions of maqāṣidiyah, such as maintaining the honor of prayer, preventing disturbances, and creating a prayer space that is conducive to achieving solemnity. In the Wahdah Islamiyah environment, the use of the sutrah has become an integral part of the culture of worship, which is instilled through halaqah, thematic studies, and the example of preachers. Cadres not only offer prayers for themselves, but also show the spirit of ta'āwun in helping others in worship. This research opens up space for the development of socio-cultural based hadith studies, especially in bringing to life sunahs that are rarely practiced in society (sunan mahjūrah), as well as strengthening a culture of worship that is based on propositions, complete understanding and contextualization in the modern Muslim community.